Surgical treatment for odontogenic keratocyst and analysis of its imaging and histopathological characteristics: Case report (Research, Society and Development, 2024)
The Odontogenic Keratocyst (OK) is a lesion that affects the bones of the mandible and maxilla, of slow growth and asymptomatic. It originates from the odontogenic tissue by the proliferation of mesenchymal tissue, epithelial tissue, or both, with keratin production inside. OK treatment takes place in different stages and therapeutic approaches, therefore, the objective of this article is to describe, through a case report, the treatment performed for an OK from the completion of marsupialization, the surgical approach performed, and the two-year postoperative follow-up in a 15-year-old male patient. The lesion was radiolucent, unilocular, with a radiopaque halo, and anteroposterior growth without destruction of the cortical bone and the initial clinical approach consisted of performing an aspiration puncture and incisional biopsy whose histopathological analysis confirmed the diagnosis of OK. Therefore, marsupialization was performed with a cannula to stimulate the bone neoformation process and reduce the size of the lesion to be favorable to completely remove it, in addition to providing a safety margin to the adjacent noble structures. Six months after the decompression of the lesion, the patient underwent surgical enucleation of the lesion associated with peripheral osteotomy. The radiographic aspect, 2 years after the surgery, shows locais bone neoformation, the integrity of noble structures such as the mandibular canal, and no evidence of lesion recurrence. The patient will be followed up for another 3 years, every 6 months.